Performance analysis of a commercial aircraft liquid hydrogen storage system - Ebrahimi, Alireza; Rolt, Andrew Martin; Sanders, Drewan S.; Schreiner, B. Deneys J. (MDPI, 2025)
Liquid hydrogen (LH2) fuel system architectures for aviation remain at low Technology Readiness Levels (TRLs) due to limited experimental data and the challenges of modelling cryogenic hydrogen’s behavior. This paper presents a computationally efficient framework for sensitivity analysis that integrates cryogenic thermodynamics, tank geometry, external heat ingress, engine mass flow demands, and pressurization control strategies. A set of operational scenarios was modeled to demonstrate how tank pressure and temperature evolve under various control and geometric conditions, delivering five key insights: (1) Passive tank self-pressurization leads to continuous pressure rise and subcooled liquid. (2) LH2 withdrawal alone may not fully stop pressurization with high heat ingress. (3) Gaseous hydrogen (GH2) injection stabilizes pressure only up to moderate heat ingress during LH2 extraction. (4) The addition of venting enables full pressure control. (5) Tank geometry and heat flux govern transient behavior. Spherical tanks show slower pressure and temperature rise than cylindrical ones, and both geometries maintain near-constant pressure at low heat flux. These insights offer practical guidance for designing reliable and thermally stable LH2 storage systems for future aircraft applications, paving the way towards sustainable and zero-emission aviation.
Keywords: liquid hydrogen; LH2; fuel system; aircraft; cryogenic tank; storage system